PERSEPSI SISWA TENTANG PENGGUNAAN GAME DALAM PEMBELAJARAN BAHASA INDONESIA DI SMAN 2 PASAMAN - Tilova, Rika Krisna; Marni, Silvia; Alfiriani, Adlia (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2025)
This research aims to explore students' perspectives on the use of technology-based educational games in learning Indonesian language activities at SMAN 2 Pasaman. The research method used is qualitative with a case study approach. Data was collected through an online questionnaire distributed to 98 tenth-grade students. The findings reveal that although the teaching methods used by teachers are still dominated by conventional approaches, the majority of students (87%) agree that educational games assist them in the learning process. Students consider educational games to make learning activities more exciting, interactive, and enjoyable. However, some students also express doubts about the effectiveness of educational games, primarily because they have never tried them or are concerned about being distracted from the learning material. Overall, the research results indicate that educational games have significant potential to enhance the quality of the Indonesian language learning process, although their implementation needs to be improved among educators.